The role of ethnicity, biological sex, and psychotropic agents in early and late onset Alzheimer’s disease - Miller, Alyssa; Desai, Ashna; Roley, Laurie Theriot; Goodwin, Richard L.; Nathaniel, Adebobola I.; Nathaniel, Thomas I. (Frontiers in Aging Neuroscience, 2022)
Objective: This study investigates differences in pharmacological and demographic factors among males and females patients with Late-onset Alzheimer’s disease (LOAD) and Early-onset Alzheimer’s disease (EOAD). Method: Data are from 10,126 AD patients, 9,290 were diagnosed with LOAD, while 836 were diagnosed with EOAD. Data were collected from the Prisma Health Upstate Alzheimer’s patients registry between 2016-2021. The logistic regression analysis was used to assess the association between pharmacological and demographic factors with males and females with LOAD and EOAD. Results: In the adjusted analysis for males, patients that were administered memantine [odd ratio (OR)=1.588, 95% CI, 1.175-2.145, P=0.003], and buspirone [OR = 1.971, 95% CI, 1.221-3.183, p=0.006] were more likely to be associated with EOAD, while increasing age [OR = 0.816, 95% CI, 0.799-0.834, P<0.001] was associated with LOAD. Females patients with a history of alcohol(ETOH) use were more likely to be associated with EOAD, while increasing age [OR = 0.845, 95% CI, 0.834-0.857, P<0.001], treatment with memantine [OR = 0.774, 95% CI, 0.627-0.956, p=0.017], African Americans [OR = 0.621, 95% CI, 0.462 – 0.835, p=0.002] and tobacco use [OR = 0.529, 95% CI, 0.424-0.660, p<0.001] were associated with LOAD. Conclusion: Our findings identified specific demographic and pharmacological factors associated with males and females with LOAD and EOAD. These findings suggest the need to develop strategies to eliminate disparity in the care of LOAD or EOAD patients.